METODE PENGAJARAN NAHWU DALAM PENGAJARAN BAHASA ARAB - Ahmad Sehri (Hunafa: Jurnal Studia Islamika, 2010)
This article deals with the method of teaching nahw in teaching Arabic. There are two common methods of teaching nahw in Arabic; they are method of al-qiyasiyyah (method of sample) and method of al-istiqrâiyyah (method of enduction). However, these two methods have their own advantages and disadvantages. Therefore, in teaching nahw, the teachers of Arabic should combine the two methods of teaching nahw based on the condition of the students the teachers will teach.Kata Kunci:    pengajaran nahwu,  metode analogis, metode induktif, i`râb, binâ’